Albania Trade Challenges of Regional and European Integration - Qefalia, Anduena (Mediterranean Journal of Social Sciences, 2012)
This research paper gives an overview of Albania`s opening of its trade towards the European market and provides somerecommendations so that the Albanian economy can at its best benefit from the European integration by strengthening its economy andmaking use of the potential that it has. Albania is currently pursuing a path of greater Euro-Atlantic integration, with primary long termgoal to gain EU membership and to promote closer bilateral ties with its neighbors. Its economy has improved substantially over therecent years and has outperformed many other countries in the region. However, the liberalization of the Albanian economy so far,though overall positive, has not enabled Albania to gain a competitive advantage. Because of the tremendous impact the integrationprocesses have in themselves in liberalizing trades, this research paper puts forward arguments that Albania, should, as first makestructural reforms to boost competition and improve the business climate. In addition, Albania should benefit every opportunity towards awider trade volume, such as a common Albania – Kosova trade by developing single fiscal policies, financial infrastructure, labor trade,custom regulations and common institutional development, leaving open doors to Macedonia integration too. In this respect, heavyinvestments in the country’s main road corridors have contributed to improved transportation conditions. Yet, similar large-scaleinfrastructure investments are needed to further improve Albania’s road transportation corridors and railway system as well as expandthe capacity of its sea ports and airports. Lastly (the milestone), given its biggest wealth, the geographical position, this paper suggestsAlbania make attempts to raise those branches of industry which would naturally fit into the European trade. In this respect, it can atbest, act as a transit point of biggest energetic networks and other continental networks, which will open doors to further development ofservice business sector in Albania.